Anna Maria Guasch and her contribution to the global art system (REVISTA NODO, 2024)
Anna Maria Guasch has been key in building a global art system, highlighting the role of others—traditionally marginalized artists, cultures, and practices—in developing a more inclusive and diverse vision of contemporary art. Based on her research on globalization processes in art, Guasch has highlighted the importance of broadening perspectives to encompass narratives and aesthetics from different geographies and contexts —including feminism— questioning the predominance of traditional power centers and promoting a plural vision of art. Her work is traced in the line of a plethora of art historians and curators —a view from Europe— who, from reflective and critical points of view, declaim in the era of the global the inclusion of the art of others (Levinas) in a process that seeks to integrate them equally into art circuits. This view is consolidated today with the curatorship of Adriano Pedrosa for the Venice Biennale 2024, with his exhibition Stranieri Ovunque – Foreigners Everywhere (Biennale di Venezia).
Keywords: Contemporary Art; Globalized circuits; Curators; Art historians; Art system